Beeswax as phase change material to improve solar panel's performance - Thaib R.; Rizal S.; Riza M.; Mahlia T.M.I.; Rizal T.A. (Institute of Physics Publishing, 2023)
Efficiency; Food products; Numerical analysis; Photovoltaic cells; Solar cell arrays; Solar concentrators; Solar power generation; Solar radiation; Waxes; Wind; Electrical efficiency; Maximum output power; Maximum temperature; Output voltages; Photovoltaic panels; PV panel; Solar panels; Wind speed; Phase change materials